Óleo essencial de aloysia triphylla (l'hérit) britton para jundiás: crescimento, transporte, parâmetros bioquímicos, metabólicos e oxidativos - Zeppenfeld, Carla Cristina (2014)
The addition of plant extracts in diet led to weight gain in some species fish. The essential oil of Aloysia triphylla (EO) has anesthetic and sedative action for fish and reduces stress handling. Thus, the present study aimed to evaluate the effect of the EO as an additive in animal feed and transportation of silver catfish Rhamdia quelen in relation to growth, intestinal morphology, metabolic and oxidative parameters, In the first experiment, the fish were be divided into three groups: 0 (control), 30 or 40 μL/L EO added to water. The fish were transported in plastic bags for 6 hours and at the end, survival, water quality and ionoregulatory and biochemical parameters were evaluated. In the second were added to the food and different concentrations of OE (0, 0.25, 0.5, 1.0 and 2.0 mL/kg) the growth of silver catfish was observed for 60 days and at the end morphological and immunohistochemical analysis of gut was performed. The addition of EO in the water of transport silver catfish and reduces stress and the suggested concentration is 40 μL /L. The addition of 2.0 mL OE per kg of diet increased in growth and its use is recommended as a feed additive for silver catfish.